Tindak Tutur Ilokusi Komunitas Waria di Pasar Ujung Gading Kabupaten Pasaman Barat - Juliatri, Juliatri; Agustina, Agustina (Universitas Negeri Padang, 2012)
The purposes of this study were to describe the form, the function, and the context of transvestite community’s ilokusionary speech act in the market of Ujung Gading, the regency Pasaman Barat. Data were collected by using record technique. The subject of this study was the community of transvestite while the object was the sentences that contain the ilokusionary speech act. However, the finding of this study showed five forms of ilokusionary speech act, four functions of ilokusionary speech act and the context of this speech act. First, the five forms of ilokusionary speech act were (1) assertive speech act which contains of informing, reporting, explaining, demanding, and sighing. (2) directive speech act that consists of commanding, requesting, prohibiting, asking, ordering and threatening. (3) komisif speech act which involves bargaining and promising. (4) expressive speech act that consists of observing, expressing thanks, forgiving, insulting, expressing sad, praising and defaming. (5) declarative speech act consists of rejecting. Second, the four functions of ilokusionary speech act were (1) competitive function, (2) convivial function, (3) collaborate function, (4) conflicting function. Third, the context of transvestite community’s ilokusionary speech act that related to place, time, atmosphere and activity when the data was collected.